Social Justice and Human Development: New Systemic Perspectives - Francesca Franceschelli (Formazione & Insegnamento, 2022)
When we talk about social justice, we must remember that its focus is on the other since it regulates the relationships between subjects, assigns to each one what is due to him/her and guarantees dignity. February 20, 2021 was an opportunity, also in light of the effects of the global epidemic from Covid-19, to ask what has been implemented and what can be planned to ensure that the opportunities for dignified development are not the prerogative of a few. Think of the population groups that are part of the third and fourth age and that, according to the Agenda2030, in 2050 will represent 22% of the global population. We could think of support interventions, of professional figures such as managers and consultants of the third and fourth age who can develop effective plans to support the elderly in order to promote solidarity between generations and activate the full potential of those who live a different age, rich in time and experience.